Oxidised low‐density lipoprotein, a possible distinguishing lipid profile biomolecule between prostate cancer and benign prostatic hyperplasia - Asare, G.A.; Owusu‐Boateng, E.; Asiedu, B.; Amoah, B.Y.; Essendoh, E.; Otoo, R.Y. (Andrologia, 2019)
Benign prostatic hyperplasia (BPH) and prostate cancer (PCa) share common conditions such as lower urinary tract symptoms (LUTS) and dyslipidaemia. Whether an extensive lipid profile analysis could discriminate between BPH and PCa was the objective. Thirty‐six (36) BPH and twenty (20) PCa outpatients of a urology clinic plus forty (40) controls without LUTS, but normal PSA, were recruited. Body mass index (BMI), lipid profile (total cholesterol [CHOL], triglycerides [TG], high‐density lipoprotein [HDL], very‐low‐density lipoprotein [VLDL], low‐density lipoprotein [LDL] and Castelli's risk index I [CR I] [TC/HDL]), oxidised LDL, apolipoprotein E, ceramide and PSA were determined. Mean ages for BPH, PCa and control were 69 ± 13, 67 ± 10 and 53 ± 7 years respectively. Most parameters apart from BMI and HDL were significantly different compared to the control group. oxLDL for BPH versus control, PCa versus control and BPH versus PCa was significant (p < 0.001, p = 0.02 and p < 0.001 respectively). Ceramide showed significant group differences. Between BPH and PCa, total cholesterol, LDL and Apo E were significantly different (p = 0.00, p = 0.01 and p = 0.03 respectively). Apo E could potentially be a discriminating biomarker. Receiver operating characteristic curves for TPSA, Apo E and oxLDL demonstrated sensitivity of 69.44 and specificity of 88.24 for oxLDL, hence more discriminatory.
Research Article
Keywords: Apo E; benign prostatic hyperplasia; lipid profile; prostate cancer